DEVELOPMENT OF PEDAGOGICAL REFLECTION POTENTIAL - PRIKHODA, IRINA V. (Челябинский гуманитарий, 2025)
Reflection is one of the promising areas of research in modern humanities. This article explores the historical dynamics of understanding and researching the phenomenon of reflection in the context of psychological and pedagogical thought from ancient times to the present day, and highlights the importance of incorporating reflective activities into the modern educational process. The relevance of this research is driven by several factors. Firstly, the current demands on professionals, which include continuous professional growth, self-education, and lifelong learning, necessitate active reflection. Secondly, the limited knowledge and insufficient development of reflection skills at all levels of the educational system. The pedagogical potential of reflection has historical roots that go back to the philosophical ideas of the ancient era. Since the 20th century, psychology has proposed numerous reflective techniques and practices that have become widely used in educational settings. In today’s educational environment, reflection has gained significant importance. The intensive use of reflective methods in university training is a necessary condition for achieving the goals of modern education, such as increasing the intellectual and professional potential of individuals, enhancing self-awareness and independence, improving communication competence and social mobility, optimizing the integration of individuals into social structures, implementing the principle of continuous education and professional growth, and promoting continuous self-improvement. However, existing research does not provide a comprehensive understanding of reflection, necessitating further in-depth study of this phenomenon.